Computer mouse use predicts acute pain but not prolonged or chronic pain in the neck and shoulder. Issue 2 (6th August 2007) - Andersen, J H; Harhoff, M; Grimstrup, S; Vilstrup, I; Lassen, C F; Brandt, L P A; Kryger, A I; Overgaard, E; Hansen, K D; Mikkelsen, S
Abstract : Background: Computer use may have an adverse effect on musculoskeletal outcomes. This study assessed the risk of neck and shoulder pain associated with objectively recorded professional computer use. Methods: A computer programme was used to collect data on mouse and keyboard usage and weekly reports of neck and shoulder pain among 2146 technical assistants. Questionnaires were also completed at baseline and at 12 months. The three outcome measures were: (1) acute pain (measured as weekly pain); (2) prolonged pain (no or minor pain in the neck and shoulder region over four consecutive weeks followed by three consecutive weeks with a high pain score); and (3) chronic pain (reported pain or discomfort lasting more than 30 days and "quite a lot of trouble" during the past 12 months). Results: Risk for acute neck pain and shoulder pain increased linearly by 4% and 10%, respectively, for each quartile increase in weekly mouse usage time. Mouse and keyboard usage time did not predict the onset of prolonged or chronic pain in the neck or shoulder. Women had higher risks for neck and shoulder pain. Number of keystrokes and mouse clicks, length of the average activity period, and micro-pauses did not influence reports of acute or prolonged pain. A few psychosocial factors predicted the risk of prolonged pain. Conclusions: Most computer workers have no or minor neck and shoulder pain, few experience prolonged pain, and even fewer, chronic neck and shoulder pain. Moreover, there seems to be no relationship between computer use and prolonged and chronic neck and shoulder pain.